Control del docente y su impacto en el desarrollo académico en los estudiantes de la unidad educativa “Guillermo Baquerizo Jiménez” del sector san Agustín, cantón Babahoyo - Alvarado Carpio, Douglas Alan (2015)
The main objective of this paper is to examine the characteristics of the institutional climate, based on the role of teachers and the academic development of students as a determinant factor in education, in the Guillermo Baquerizo Jiménez Educational Unit of the San Agustín Sector, Canton Babahoyo. The present research work has been structured in four chapters: Chapter one is the subject, problematic contextual field and at the same time it is integrated by the subject, contextual framework, problematic situation, problem approach, delimitation of research, justification and objectives. Chapter two demonstrates the theoretical or referential framework in which the analysis of the teacher and student profile is presented, approaches to the teaching profile over time, the attitudes that the teacher should have, and similar research carried out in the The category of analysis, the theoretical posture, hypotheses and sub-hypotheses and variables. Chapter three is devoted to the results of research specifically to the analysis and interpretation of results, general and specific conclusions and general and specificrecommendations. Chapter four and last is composed by the proposal of application of result, to possible solutions and alternatives of the research problem. As a conclusive part, a proposal is presented for a reflection workshop on the benefits of teacher control, with an approach that improves teacher performance, interpersonal relationships, as starting points in teaching learning processes and in academic development in the students.